Gender violence in university students: A challenge for higher education - Macarena Trujillo Cristoffanini; Universidad de Playa Ancha; Inma Pastor-Gosálbez; Universidad Rovira i Virgili (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2021)
Gender violence threatens women's human rights regardless of their status or origin. This article presents a research conducted in Chilean universities during 2019, which addresses, through a qualitative methodology, the experiences of female university students who have faced gender-based violence by their partners. With this objective, researchers explored in the first place, the emotional repercussions that this type of violence entails, as well as the trajectories and difficulties that young women must face in order to end relationships in which violence has existed. Secondly, it is analyzed the incidence of formal and informal support networks that young people have and the various levels of trust that they project. In a preeminent way, those networks stand out that, from within the educational spaces, promote the agency and autonomy of the students and impel them to abandon relations with the aggressors. The experiences collected make visible the inescapable role of higher education institutions in the fight against gender violence.